2010
DOI: 10.12681/mms.96
|View full text |Cite
|
Sign up to set email alerts
|

First record of Paraprionospio coora Wilson, 1990 (Polychaeta: Spionidae) from the Mediterranean Sea)

Abstract: The spionid polychaete Paraprionospio pinnata (Ehlers, 1901) has been widely reported from the Mediterranean Sea. We examined some specimens belonging to the genus Paraprionospio that had been collected from the Aegean Sea, the Sea of Marmara and the Spanish Mediterranean coast, and identified them as Paraprionospio coora Wilson, 1990, which is new to the Mediterranean fauna. This finding indicates that P. coora has a widespread geographical distribution in Australia, the Far East and the Mediterranean, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The examined specimens of P. coora agree well with the description of the species by YOKOYAMA et al (2010). The Greek specimens also have a small protuberance on the dorsum near the base of the third branchiae, and 2-3 pairs of apical teeth in neuropodial hooded hooks.…”
Section: Taxonomic Remarkssupporting
confidence: 82%
See 2 more Smart Citations
“…The examined specimens of P. coora agree well with the description of the species by YOKOYAMA et al (2010). The Greek specimens also have a small protuberance on the dorsum near the base of the third branchiae, and 2-3 pairs of apical teeth in neuropodial hooded hooks.…”
Section: Taxonomic Remarkssupporting
confidence: 82%
“…The closely similar species Paraprionospio pinnata (Ehlers, 1901) has a wide geographical distribution and is reported also from the western and eastern Mediterranean. However, the examination of older benthic material collected from the Aegean Sea and identified as P. pinnata revealed that the material actually belonged to P. coora (YOKOYAMA et al, 2010). SIMBOURA (1996) reported some specimens of a spionid species closely resembling P. pinnata, and assigned them to the genus Aquilaspio because of the insertion of the first pair of branchiae on the chaetiger 2.…”
Section: Materials Examinedmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Mediterranean also known from Turkey (Yokoyama et al 2010(Yokoyama et al , Çınar et al 2014, Spain , Tunisia (Zaâbi et al 2012) and the Adriatic , otherwise known from the Pacific Ocean (Australia, Far East).…”
Section: Paraprionospio Coora Wilson 1990mentioning
confidence: 99%
“…Several authors suggest that Mediterranean records of this species should be assigned to Paraprionospio coora (Yokoyama et al 2010, Simboura et al 2010.…”
Section: Paraprionospio Pinnata (Ehlers 1901)mentioning
confidence: 99%